"Click"‐Triggered Self‐Healing Graphene Nanocomposites. Issue 21 (19th September 2016) - Rana, Sravendra; Döhler, Diana; Nia, Ali Shaygan; Nasir, Mahmood; Beiner, Mario; Binder, Wolfgang H.
Abstract : Strategies to compensate material fatigue are among the most challenging issues, being most prominently addressed by the use of nano‐ and microscaled fillers, or via new chemical concepts such as self‐healing materials. A capsule‐based self‐healing material is reported, where the adverse effect of reduced tensile strength due to the embedded capsules is counterbalanced by a graphene‐based filler, the latter additionally acting as a catalyst for the self‐healing reaction. The concept is based on "click"‐based chemistry, a universal methodology to efficiently link components at ambient reaction conditions, thus generating a "reactive glue" at the cracked site. A capsule‐based healing system via a graphene‐based Cu2 O (TRGO‐Cu2 O‐filler) is used, acting as both the catalytic species for crosslinking and the required reinforcement agent within the material, in turn compensating the reduction in tensile strength exerted by the embedded capsules. Room‐temperature self‐healing within 48 h is achieved, with the investigated specimen containing TRGO‐Cu2 O demonstrating significantly faster self‐healing compared to homogeneous (Cu(PPh3 )3 F, Cu(PPh3 )3 Br), and heterogeneous (Cu/C) copper(I) catalysts. Abstract : "Click"‐triggered room‐temperature self‐healing graphene‐based nancomposites are designed. After damage, encapsulated self‐healing agents are set free and form polymeric networks via a Cu(I)‐catalyzed azide–alkyne "click" reaction. The use of highly dispersible graphene‐immobilized Cu2 O demonstrates excellent catalytic performance with extraordinary reinforcement in tensile strength, resulting in 100% crack healing at 20 °C after 36 h.